Technique and maximal skiing speed for youth cross-country skiing performance - Stöggl, Roland; Müller, Erich; Stöggl, Thomas (Frontiers in Sports and Active Living, 2023)
Numerous researches concentrate on examining and preparing high-level male cross-country skiers, with a significant number of tests being conducted on roller skis. However, there is a scarcity of research on the testing and preparation of younger male and female athletes ranging from 10 to 16 years old. The main purpose of this research was to determine if certain cross-country (XC) skiing tests and maturity status are indicators of performance in youth cross-country skiing; to examine any differences in performance between young males and females; and to establish non-invasive diagnostic tools for assessing performance. Fifty-eight young XC skiers (36 boys; 12.88 ± 1.19 yrs and 22 girls; 12.79 ± 1.09 yrs) performed specific XC skiing maximal speed tests consisting of short (50 m) flat and uphill distances (30/40 m). Results were correlated with on snow XC skiing performance (PXC) based on one skating (including an agility parcours) and one classical distance competition. The key findings of this research were: 1) Age and maturity status were associated to boys’and girls’ PXC; 2) Significant moderate to high correlations between girls’ and boys’ short duration XC skiing sprint performance 30-50 m (double poling (DP) flat and uphill, free skating, leg skating and V1 uphill skating) and PXC were revealed; 3) In general, the best prediction for PXC (Boys and Girls) was found to be the asymmetrical uphill (V1 40 m uphill) sub-technique; and 50 m DP (flat) while Boys’ PXC was determined by V1 skating and girls’ performance mainly by 50 m free skating (flat); 4) When using maturity offset as a confounding variable, boys’ and girls’ PXC was still highly associated with short duration skiing tests. In conclusion, the use of simple, non-invasive XC skiing sprint tests for evaluating PXC can be beneficial for ski clubs, specialized schools, or skiing federations in identifying and training young talented skiers. Further, this result demonstrates that skiing abilities such as short duration maximal speed and the proper use of different sub-techniques at high speeds during XC skiing is an important performance prerequisite.